Genomic epidemiology of the commercially important pathogen Renibacterium salmoninarum within the Chilean salmon industry. Issue 9 (24th July 2018) - Bayliss, Sion C.; Verner-Jeffreys, David W.; Ryder, David; Suarez, Rudy; Ramirez, Roxana; Romero, Jaime; Pascoe, Ben; Sheppard, Sam K.; Godoy, Marcos; Feil, Edward J.
Abstract : Renibacterium salmoninarum is the causative agent of bacterial kidney disease (BKD), which is a commercially important disease of farmed salmonids. Typing by conventional methods provides limited information on the evolution and spread of this pathogen, as there is a low level of standing variation within the R. salmoninarum population. Here, we apply whole-genome sequencing to 42 R. salmoninarum isolates from Chile, primarily from salmon farms, in order to understand the epidemiology of BKD in this country. The patterns of genomic variation are consistent with multiple introductions to Chile, followed by rapid dissemination over a 30 year period. The estimated dates of introduction broadly coincide with major events in the development of the Chilean aquaculture industry. We find evidence for significant barriers to transmission of BKD in the Chilean salmon production chain that may also be explained by previously undescribed signals of host tropism in R. salmoninarum . Understanding the genomic epidemiology of BKD can inform disease intervention and improve sustainability of the economically important salmon industry. This article contains data hosted by Microreact.